Variability of gross and fine motor control in different tasks in fibromyalgia patients - Nancy Brígida; David Catela; Cristiana Mercê; Marco Branco (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Fibromyalgia (FM) is normally defined as a widespread pain syndrome or disease that presents disturbances in gross and fine motor control. As a gross motor control skill, gait requires coordination, balance, and muscle strength, and it could be an essential factor for FM patients to perform daily activities. Measuring the spatial and temporal gait parameters or gait variability has been used to assess motor pathologies and identify gait disorders. The Lyapunov exponent is a non-linear measure of variability, which quantifies the ability that the system has to attenuate small perturbances, indicating that there might be a relationship between balance and spatiotemporal gait parameters. This technique has already been used for gait analysis and could be used in fine and gross daily tasks, such as the finger tapping test (FTT) or the sit-and-stand test. Inertial Measurement Units have also been used to analyze gross motor control, namely in gait variability. So, the aim of this study is to analyze and compare the variability of gross and fine motor movements between patients with FM and a control group. The sample included 20 female participants, 10 with FM and 10 without (46.150 ± 12.835 years old). To analyze gross motricity, participants were asked to perform the gait task for two minutes and the 30-second chair sit-and-stand test; and to analyze fine motor control, they were asked to perform six trials of FTT test with both hands. To collect the data, an inertial sensor (IMU) was used. FM patients showed a more irregular pattern of linear acceleration peaks than controls in both tasks. Lyapunov values in FM patients show greater instability and variability in the anteroposterior and vertical movements for gait analysis and present significantly higher variability in the anteroposterior movements when performing the sit and stand task and the finger tapping test.